2011
DOI: 10.1200/jco.2010.32.2321
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of Trastuzumab in Combination With Everolimus (RAD001) in Patients With HER2-Overexpressing Metastatic Breast Cancer Who Progressed on Trastuzumab-Based Therapy

Abstract: Purpose Trastuzumab resistance has been linked to activation of the phosphoinositol 3-kinase (PI3K) pathway. Phosphatase and tensin homolog (PTEN) is a dual phosphatase that counteracts the PI3K function; PTEN loss leads to activation of the Akt cascade and the downstream mammalian target of rapamycin (mTOR). Preclinical studies demonstrated that mTOR inhibition sensitized the response to trastuzumab in mice with HER2 overexpressing and PTEN-deficient breast xenografts. Our trial evaluated the safety and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(126 citation statements)
references
References 16 publications
(6 reference statements)
4
122
0
Order By: Relevance
“…The possible mechanisms that underlie the primary resistance of these drugs have been supposed as follows: i) activation of other signaling pathways alternative to EGFR, such as the insulin-like growth factor 1 receptor (IGF-1R) and vascular endothelial growth factor receptor (VEGFR); and ii) deregulation of downstream signaling pathways such as AKT/mTOR (2)(3)(4)(5). Recently, much research has focused on combined treatment with different signaling drugs, representing a novel strategy for cancer therapy (6)(7)(8). Here, mTOR inhibitor emerged as an attractive drug candidate due to the role of the mTOR pathway in the development of lung cancer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanisms that underlie the primary resistance of these drugs have been supposed as follows: i) activation of other signaling pathways alternative to EGFR, such as the insulin-like growth factor 1 receptor (IGF-1R) and vascular endothelial growth factor receptor (VEGFR); and ii) deregulation of downstream signaling pathways such as AKT/mTOR (2)(3)(4)(5). Recently, much research has focused on combined treatment with different signaling drugs, representing a novel strategy for cancer therapy (6)(7)(8). Here, mTOR inhibitor emerged as an attractive drug candidate due to the role of the mTOR pathway in the development of lung cancer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR inhibitors temsirolimus (Torisel; Pfizer), everolimus (Afinitor; Novartis), and ridaforolimus (Merck & Company, Inc.) have been evaluated in breast cancer, and everolimus was approved by the FDA for postmenopausal women with advanced hormone receptor-positive HER2-negative breast cancer in combination with exemestane after failure of letrozole or anastrozole [90]. Pooled data from two phase I/II studies in HER2-positive MBC patients who progressed on trastuzumab reported an RR of 15% and median PFS of 4.1 months with everolimus plus trastuzumab [91]. Two phase Ib studies of MBC patients with prior trastuzumab therapy showed PFS of 30.1 and 34 weeks with everolimus in combination with trastuzumab/vinorelbine or trastuzumab/paclitaxel, respectively [92,93].…”
Section: The Mtor Pathwaymentioning
confidence: 99%
“…The human epidermal growth factor receptor 2 (HER2) is tumour marker of breast cancer, and overexpression of HER2 is found in approximately 30% of patients with breast cancer [1]. Trastuzumab which is monoclonal therapeutic antibody against HER2 is applied to the treatment for patients with breast cancer [2][3][4]. However, the efficacy of Trastuzumab for patients with HER2-negative breast cancer and trastuzumab-resistant HER2-positive breast cancer is limited [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Trastuzumab which is monoclonal therapeutic antibody against HER2 is applied to the treatment for patients with breast cancer [2][3][4]. However, the efficacy of Trastuzumab for patients with HER2-negative breast cancer and trastuzumab-resistant HER2-positive breast cancer is limited [4,5]. Therefore, novel nanomedicine against HER2-negative breast cancer is needed.…”
Section: Introductionmentioning
confidence: 99%